Cloning of Aspergillus Niger BglA and expression of recombinant Î²-glucosidase in methylotrophic yeast Pichia Pastoris - Kamaruddin, Shazilah; Abu Bakar, Farah Diba; Md Illias, Rosli; Rabu, Amir; Said, Mamot; Hassan, Osman; Abdul Murad, Abdul Munir (Penerbit UTM Press, 2008)
Full length cDNA of bglA gene encoding Aspergillus niger ATCC10574 Î²-glucosidase was isolated and sequenced. The cDNA has a length of 2583 bp which encodes a polypeptide of 860 amino acid residues with predicted pI value of 4.6 and molecular weight of 93 kDa. Amino acid analysis of BGLA from four different isolates of A. niger, isolates ATCC10574, ATCC1015, B1 and CBS513.88, detected a total of 29 amino acids differences. The degree of differences varies between different variants, from 0.46% up to 2.9%. Around 34% of these differences were located in Î²-glucosidase two conserved domains, the glycosyl hydrolase family 3 N-terminal and the C-terminal domains. Both of the domains are important for the catalytic activity of the enzyme and these differences might contribute to different biophysical and biochemical enzyme properties. Heterologous expression of BGLA in methylotrophic yeast, Pichia pastoris has been carried out using methanol as inducer resulting in the production of recombinant protein with molecular weight around 90 kDa. Î²-glucosidase activity was detected from the culture filtrate using UVstimulated fluorescence of cleaved fluorescence substrate, 4-methylumbelliferyl-Î²-D-glucopyranoside (MUGlc). The specific activity of the crude recombinant enzyme for cellobiose hydrolysis was 18 U/mg.